The cost effectiveness of ivabradine in the treatment of chronic heart failure from the UK National Health Service perspective. Issue 13 (14th March 2014) - Griffiths, A; Paracha, N; Davies, A; Branscombe, N; Cowie, M R; Sculpher, M
Abstract : Objective: Ivabradine, a specific heart rate lowering therapy, has been shown in a randomised placebo-controlled study, Systolic HF Treatment with the If Inhibitor Ivabradine Trial (SHIf T), to significantly reduce the composite end point of cardiovascular death and hospitalisation for worsening heart failure (HF) in patients with systolic HF who are in sinus rhythm and with a heart rate ≥70 bpm, when added to optimised medical therapy (HR: 0.82, 95% CI 0.75 to 0.90, p<0.0001). We assessed the cost effectiveness of ivabradine, from a UK National Health Service perspective, based on the results of SHIf T. Methods: A Markov model estimated the cost effectiveness of ivabradine compared with standard care for two cohorts of patients with HF (heart rate ≥75 bpm in line with the EU labelled indication; and heart rate ≥70 bpm in line with the SHIf T study population). Modelled outcomes included death, hospitalisation, quality of life and New York Heart Association class. Total costs and quality adjusted life years (QALYs) for ivabradine and standard care were estimated over a lifetime horizon. Results: The incremental cost per additional QALY for ivabradine plus standard care versus standard care has been estimated as £8498 for heart rate ≥75 bpm and £13 764 for heart rate ≥70 bpm. Ivabradine is expected to have a 95% chance of being cost-effective in the EU licensed population using the current National Institute for Health and Care Excellence cost effectiveness threshold of £20 000 per QALY. These results were robust in sensitivity analyses. Conclusions: This economic evaluation suggests that the use of ivabradine is likely to be cost-effective in eligible patients with HF from a UK National Health Service perspective.